IMPROVING THE QUALITY OF SHARIA INSURANCE AGENTS THROUGH TECHNOLOGY OPTIMALIZATION AS A SHARIA-BASED MARKETING MEDIUM - Novi Indriyani Sitepu; Saparuddin Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The physical, the intellectual and the spiritual qualities of the agent is creates agent competence so that they can compete in the sharia insurance marketing business. Competition for human performance is currently over helmed by the ease of technology through the internet mediawhich poses a challenge for agents to be able to take advantage of technology. The high competition needs to be framed using sharia views in order to maintain Islamic values. This phenomenon then makes insurance agents as a technology driver in marketing the shariah insurance business in sharia companies in the Nort Sumatera. This stydy uses a qualitative method with a construction approach. Primary research data were obtained through interviews with agency company leaders and MDRT agents to found the quality agens. Secondary data were obtained from literature studies. The results showed that the physical quality of Islamic insurance agents is very influential in marketing products but in technology optimizationit has less effect. While intellectual quality has an effect on the ability of agent technology optimization, then spiritual quality to greatly effect the ability to optimize technology. Sharia insurance agents at takaful and prudential companies have optimized technology as their marketing medium frame by sharia views